The role of multi-stakeholder forums in subnational jurisdictions: Methods training manual and tools for in-depth research - Sarmiento Barletti, Juan Pablo; Larson, Anne M. (Center for International Forestry Research, 2019)
This Methods training manual and tools for in-depth field research sets out the rationale and method for CIFOR s research on multi-stakeholder forums (MSFs). It was specifically designed to examine MSFs set up to address land use and land-use change at the subnational level in Brazil, Ethiopia, Indonesia, and Peru. This manual should be read in tandem with the project s Framing literature review for in-depth field research. MSFs are purposely organized interactive processes that bring together a range of stakeholders to participate in dialogue, decision-making and/or implementation regarding actions seeking to address a problem they hold in common, or to achieve a goal for their common benefit. The growth of MSFs related to land use/land-use change reflects the awareness that environmental problems cannot be addressed without the effective engagement of the actors that determine land-use practices on the ground; nor can such problems be resolved within a conservation community when the drivers are located in other sectors. MSFs may produce more effective and sustainable outcomes by getting sectors and actors that have commonly held contradictory development priorities to coordinate and align goals through discussion, negotiation and planning. Nevertheless, MSFs may also be an expedient way to implement top-down approaches and create the illusion of participation. Scholars and activists note that MSF may reify top-down approaches, and take the participation of local stakeholders for granted in box-ticking exercises to please donors. This research is timely because MSFs have received renewed attention from policy makers and development and conservation practitioners, in light of the growing perception of urgency to address climate change and transform development trajectories. The comparative project aims to contribute empirically to the study of MSFs and similar participatory processes. We hope others will find this manual useful for designing similar research initiatives.